Digital Sor-Singgih: A Narrative Inquiry into Ethnotech-Pragmatics among Youth in Denpasar - Wedananta, Kadek Adyatna; Budiarta, I Komang (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The‍‌ research broadens the Ethnotech-Pragmatics conceptual model, initially introduced by Wedananta (2023), for investigating how the young people of Denpasar juggle the tensions between Balinese cultural values and the digital world of Instagram. This‍‌‍‍‌‍‌‍‍‌ paper employs a narrative qualitative method so as to reveal the